2003
DOI: 10.5380/avs.v8i2.4034
|View full text |Cite
|
Sign up to set email alerts
|

EXAME MICOLÓGICO E ACOMPANHAMENTO CLÍNICO DE BOVINOS INFECTADOS PELA FORMA LATENTE DO Trichophyton verrucosum (BODIN, 1902)

Abstract: RESUMO -Com o objetivo de se determinar o período de latência da tricofitose bovina sob condições naturais de infecção, bem como testar a utilidade da escova de unha de uso humano, foram examinados 80 bovinos sadios, com menos de 3 meses de idade, que estavam em contato com animais doentes. O dermatófito Trichophyton verrucosum (Bodin 1902) foi isolado em cultivos micológicos de 32 animais (40 %), dentre os quais 25 foram acompanhados clinicamente durante 16 semanas; destes 22 adoeceram com sintomatologia cara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 2 publications
(3 reference statements)
0
4
2
2
Order By: Relevance
“…Based on the lack of any statistically significant support for the risk factors we examined, our results show that calves of any sex, breed, age, and of any of the farm condition considered are highly exposed to risk of T. verrucosum infection. With respect to results of comparable studies, the present infection rate is considerably higher than the 47.8% found in Jordan (Al‐Alani et al., 2002), 17.1–58.6% in Japan (Takatori et al, 1993), 25% in Spain (Cabañes et al, 1997), 32.3% in Iran (Khostravi and Mahmoudi, 2003), and 40–44% in Brazil (Ollhoff, 2003; Silveira et al, 2003). In Italy, total prevalence values previously reported from different cattle populations were 18.7% with T. verrucosum isolated in 26 out of 28 ringworm infected farms (Mantovani and Moranti, 1977), 4.5–19% (Moretti et al, 1998), and 48.7% (Galuppi et al, 2002).…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…Based on the lack of any statistically significant support for the risk factors we examined, our results show that calves of any sex, breed, age, and of any of the farm condition considered are highly exposed to risk of T. verrucosum infection. With respect to results of comparable studies, the present infection rate is considerably higher than the 47.8% found in Jordan (Al‐Alani et al., 2002), 17.1–58.6% in Japan (Takatori et al, 1993), 25% in Spain (Cabañes et al, 1997), 32.3% in Iran (Khostravi and Mahmoudi, 2003), and 40–44% in Brazil (Ollhoff, 2003; Silveira et al, 2003). In Italy, total prevalence values previously reported from different cattle populations were 18.7% with T. verrucosum isolated in 26 out of 28 ringworm infected farms (Mantovani and Moranti, 1977), 4.5–19% (Moretti et al, 1998), and 48.7% (Galuppi et al, 2002).…”
Section: Discussioncontrasting
confidence: 45%
“…In the present study, T. verrucosum was isolated from 80.4% of asymptomatic calves and results of a follow-up study revealed that T. verrucosum can remain on the skin of 88% of all apparently healthy calves for 2-8 weeks before clinical signs develop. In addition, in the same study, 12% of all apparently healthy calves did not develop skin lesions within 140 days after the first examination (Ollhoff, 2003). Therefore, some infected calves harbour the organism on their coat before there are visible signs of infection and it is possible that some of them have a degree of natural immunity that prevents develop-ment of lesions.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…T. verrucosum, a espécie mais comumente isolada de casos clínicos e adaptada ao bovino, foi isolado em baixas frequências (LONDERO et al, 1970;SILVEIRA et al, 2003). Todavia, essas frequências aumentam quando há contato com animais doentes ou presença de animais já recuperados da doença, os quais veiculam os conídios do fungo, atuando como disseminadores e perpetuadores da enfermidade (LONDERO et al, 1970;TAKATORI et al, 1993;OLLHOFF, 2003). Surtos de dermatofitose em bovinos, causados por T. verrucosum, têm sido observados no Rio Grande do Sul, afetando tanto animais adultos como jovens, durante os meses de outono e inverno, com prevalências que variam de 7,5% a 42,8% (PEREIRA & MEIRELES, 2007).…”
Section: Introductionunclassified